2020
DOI: 10.3390/cells10010036
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Rapid Non-Enzymatic Procedure Allows the Isolation of Structurally Preserved Connective Tissue Micro-Fragments Enriched with SVF

Abstract: The stromal vascular fraction (SVF) consists of a heterogeneous population of stem and stromal cells, generally obtained from adipose tissue by enzymatic digestion. For human cell-based therapies, mechanical process methods to obtain SVF represent an advantageous approach because they have fewer regulatory restrictions for their clinical use. The aim of this study was to characterize a novel commercial system for obtaining SVF from adipose tissue by a mechanical approach without substantial manipulations. Lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…In non‐enzymatic separation processes, Victor [24] reported that the number of cells in the SVF aspirates obtained using the ultrasonic cavitation method was 3.93–12.8 × 10 6 and the cell viability rate was 86.5–96.2%. Conversely, Busato et al [7] reported the average number of non‐enzymatic yet free‐nucleated cells in SVF, obtained by the tumescent anaesthesia method, was 4.1 × 10 4 . In the literature, no study has reported the methods of obtaining SVF using peripheral local anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In non‐enzymatic separation processes, Victor [24] reported that the number of cells in the SVF aspirates obtained using the ultrasonic cavitation method was 3.93–12.8 × 10 6 and the cell viability rate was 86.5–96.2%. Conversely, Busato et al [7] reported the average number of non‐enzymatic yet free‐nucleated cells in SVF, obtained by the tumescent anaesthesia method, was 4.1 × 10 4 . In the literature, no study has reported the methods of obtaining SVF using peripheral local anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some authors reported a reduced level of cell contamination after mechanical isolation when compared to enzymatic treatment [32]. The main pitfall is represented by the higher content of blood mononuclear cells, which appeared to be related to the location of ASCs precursors and pericytes in the perivascular niches, requiring releases [23,[33][34][35][36]. In the authors' opinion, the only real advantage of enzymatic digestion using collagenase to isolate and extract the SVF from the adipose tissue is that eventually, it can offer the possibility of obtaining the tissue breakdown to the single cell.…”
Section: Methods Of Isolationmentioning
confidence: 99%
“…ASCs were isolated from human lipoaspirate of healthy donors (women of ages between 35 and 45 years) after informed consent, following the protocol described by Peroni et al [22] and Busato et al [23], using an enzymatic method [18,19]. flask with complete growth medium.…”
Section: Isolation and Seeding Of Adipose-derived Stem Cellsmentioning
confidence: 99%